From Burnout to Belonging: A Sequential Mixed Methods Study of Comprehensive Support Structures for Online Adjunct Faculty - Reed, Rheanna; Carriere, Jennifer; Pipoly, Laura; Bennett, Anthony (Online Learning, 2025)
Online adjunct faculty encounter many unique challenges while continuing to play a pivotal role in higher education. These include burnout, high course loads coupled with long work hours, increased student numbers, excessive administrative work, lack of training, high academic competition, role ambiguity, and lack of wellness-promoting activities in higher education. These challenges could potentially set back student outcomes. Given the growing dependence on online adjunct faculty, delving into these complex dynamics is crucial. This research aimed to uncover the perceptions of the effectiveness of supportive best practices and to explore the evolution of these practices from the perspectives of adjunct faculty, university leaders, and archived documents like policies and procedures. This exploratory case study design offered a holistic view of support structures through the perspectives of online adjunct faculty, university leadership, and support departments using an open-ended questionnaire and archival documents. Thematic analysis and triangulation allowed patterns and themes to emerge regarding current practices' efficacy and pinpoint improvement areas. This increased understanding can lead to enhanced teaching practices, better student learning experiences, success, and consideration for best supportive practices within online higher education.